Immediate and long-term electrophysiological biomarkers of antidepressant-like behavioral effects after subanesthetic ketamine and medial prefrontal cortex deep brain stimulation treatment - Bergosh, Matthew; Medvidovic, Sasha; Zepeda, Nancy; Crown, Lindsey; Ipe, Jennifer; Debattista, Lauren; Romero, Luis; Amjadi, Eimon; Lam, Tian; Hakopian, Erik; Choi, Wooseong; Wu, Kevin; et al. (Frontiers in Neuroscience, 2024)
Both ketamine (KET) and medial prefrontal cortex (mPFC) deep brain stimulation (DBS) are emerging therapies for treatment-resistant depression, however a thorough understanding of their mechanisms of action and efficacy biomarkers have yet to be established. This study investigates immediate and long-term mPFC electrophysiological correlates of both ketamine and mPFC DBS's antidepressant-like effects, and explores the effects of combinatorial treatment.To create the depression model, male Sprague Dawley rats were given corticosterone or vehicle for 21 days. In the last 7 days, animals receiving CORT were treated with mPFC DBS, ketamine, both, or neither. All groups were then tested across an array of behavioral tasks. Local field potentials of the mPFC were recorded throughout the experiment. DBS treatment immediately suppressed relative low gamma power and improved long-term performance of memory-based cognitive tasks, both of which correlated with rescued apathy-like behavior in the Groom Test (GT). In contrast, following ketamine treatment, immediate and sustained suppression of sample entropy (a measure of signal complexity) correlated with rescue of the GT. In the combinatorial group these changes were absent, and the GT was not rescued. Despair-like behavior in the Forced Swim Test was rescued by all three treatments. Our findings support the utility of low gamma power, sample entropy, and cognitive tests in the search for mechanisms and biomarkers of depression and novel treatments. The complex interaction between the two treatments studied here enhanced our understanding of their separate mechanisms and demonstrated that the combination of these treatments may be detrimental to certain aspects of therapeutic efficacy.